Product differentiation, the volume of trade and profits under Cournot and Bertrand duopoly - David R. Collie; Vo Phuong Mai Le (Cardiff University, Cardiff Business School, 2011)
This paper analyses how product differentiation affects the volume of trade under duopoly using Shubik-Levitan demand functions rather than the Bowley demand functions used by Bernhofen (2001). The Shubik-Levitan demand functions have the advantage that an increase in product differentiation does not increase the size of the market as happens with the Bowley demand functions. It is shown that the volume of trade in terms of quantities is decreasing in the degree of product differentiation when the trade cost is relatively low, but increasing in the degree of product differentiation when the trade cost is relatively high.
Keywords: F12; F13; 330; Product Differentiation; Cournot Oligopoly; Bertrand Oligopoly; Unternehmensplanung; Produktdifferenzierung; Gewinn; Duopol; Theorie